2010
DOI: 10.1007/s10528-010-9341-4
|View full text |Cite
|
Sign up to set email alerts
|

Rangewide Genetic Diversity in Natural Populations of Chinese Pine (Pinus tabulaeformis)

Abstract: Thirteen natural populations from throughout the range of the Chinese pine (Pinus tabulaeformis Carr.) were examined using inter-simple sequence repeat markers to characterize the genetic structure at the species level and to compare the extent and distribution of genetic variation among central, intermediate, and marginal populations. Although the total genetic variation in the Chinese pine was mainly maintained within populations, the genetic differentiation among populations was significant (P < 0.001). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
3
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 23 publications
(29 reference statements)
1
6
3
1
Order By: Relevance
“…Total genetic diversity for P. nigra in this study ( H E = 0.175) was lower than other Pinus species similarly researched with ISSR markers, such as Pinus tabuleaformis (0.4152, [18]), Pinus koraiensis (0.3477, [19]), Pinus sibirica (0.2699, [20]), Pinus sylvestris (0.2620, [21]; 0.217–0.310, [22]), and higher than Pinus squamata (0.029, [23]). The differences in the levels of genetic diversity among these species may be related to geographic distribution, number of population tested, population size of the species and the effect of climate changes during the last glacial maximum.…”
Section: Resultsmentioning
confidence: 53%
“…Total genetic diversity for P. nigra in this study ( H E = 0.175) was lower than other Pinus species similarly researched with ISSR markers, such as Pinus tabuleaformis (0.4152, [18]), Pinus koraiensis (0.3477, [19]), Pinus sibirica (0.2699, [20]), Pinus sylvestris (0.2620, [21]; 0.217–0.310, [22]), and higher than Pinus squamata (0.029, [23]). The differences in the levels of genetic diversity among these species may be related to geographic distribution, number of population tested, population size of the species and the effect of climate changes during the last glacial maximum.…”
Section: Resultsmentioning
confidence: 53%
“…Shannon's index (I) with a value of 0.382 indicated that the examined populations of pitch pine were characterized by more than threefold higher genetic variability as compared to the variability in P. sylvestris (I = 0.158) [39], while similar values were found for P. tabulaeformis (I = 0.3078) [49]. The value of total genetic diversity (H T = 0.262) was lower than that in P. koraiensis (H T = 0.348) [4] and P. tabulaeformis (H T = 0.415) [41], as well as the alpine populations of P. sylvestris (H T = 0.310), but it was similar to the values obtained for the populations of Scots pine derived from the Apennines (H T = 0.217) [40].…”
Section: Discussionmentioning
confidence: 59%
“…However, a disadvantage of this technique is the dominant character of the obtained products. Despite this disadvantage, the ISSR technique has been used to determine the level of genetic diversity in many forest tree species of the genera Abies [38], Pinus [4,[39][40][41], Picea [42], Pseudotsuga [43], Taxus [44], Fagus [45], Quercus [46], and others. There are, however, no studies on ISSR analysis in pitch pine.…”
Section: Discussionmentioning
confidence: 99%
“…The highest H E values were observed in the Cong Troi population (0.250) and the lowest in the Hon Giao population (0.200; Table 5). Total genetic diversity for P. krempfii in this study (H E = 0.229) was higher than P. nigra (H E = 0.175) and Pinus squamata (H E = 0.029) (Zhang et al, 2005;Rubio-Moraga et al, 2012) and lower than some other Pinus species, which were similarly analyzed with ISSR markers, such as Pinus tabulaeformis (H E = 0.4152; Wang and Hao, 2010) Table 5). In all populations in the current study, five of the eight loci showed significant heterozygote deficiency.…”
Section: Genetic Divergencementioning
confidence: 49%